The Eschatology of Tertullian - Pelikan, Jaroslav 1923-2006 (1952)
One of the most important results of the New Testament study that has gone on during the past generation is its realization that the theology of the New Testament is unintelligible outside the context of its eschatological message. The precise meaning of that message is still the subject of much investigation and controversy, but its importance has become a matter of general agreement among New Testament students. Much less general is the realization of the implications of this insight for other areas of theological concern. Rudolf Bultmann's recent essay on mythology and the New Testament has served to raise again the question of the relevance of New Testament eschatology for systematic theology. That question has far-reaching implications for the study of the history of theology as well, implications with which historical theology has not yet come to terms. The relation between primitive Christian eschatology and the development of ancient Christian theology is a problem deserving of more study than the standard interpretations of the history of dogma have given it, for it can help iiluminate the origins of such dogmas as the Trinity and ancient Christology. Among the historians of dogma, only Martin Werner has taken up the problem in great detail, and his discussion of it has not yet issued in any new historico-theological synthesis.
Keywords: Eschatologie; Theologie; Tertullian; escatology; Theology